Final years of life and seasons of death of woolly mammoths from Wrangel Island and mainland Chukotka, Russian Federation. (25th July 2017) - El Adli, Joseph J.; Fisher, Daniel C.; Vartanyan, Sergey L.; Tikhonov, Alexei N.
Abstract: The tusks of proboscideans contain a continuous record of growth throughout much of an individual's life. Proximal portions of isolated tusks from five individuals of Mammuthus primigenius from Chukotka and Wrangel Island, Russian Federation, were analyzed to extract life history information from the last years of life. All five individuals are identified as adults based on the shallowness of their pulp cavities and the reverse-taper of the tusks proximal to the gingival margin. Given this, these individuals are interpreted as female due to the relatively small circumference of their tusks. However, based on these features, there appears to be a range in ontogenetic age among these individuals. Radiocarbon dating of the specimens yields absolute age estimates ranging from approximately 5000 to 7500 C 14  yr BP (5600 to 8550 cal BP) for the Wrangel Island specimens and 15, 000 to 26, 000 C 14  yr BP (18, 350 to 30, 950 cal BP) for the Chukotka specimens. Isotopic, thin section, and x-ray microtomographic analyses were performed on each specimen to determine the boundaries between years and to understand both inter- and intra-annual variation in tusk growth. Variation within and between years is then used to interpret season of death and relevant life history information for each individual. Each tusk segment recorded approximately five to nine years of growth. Based on the patterns observed in dentin density and comparison with previous years, all five individuals are interpreted as having died in late winter. With the exception of one specimen representing a younger individual, all of the tusks display a sinusoidal change in annual appositional tusk growth over an interval of approximately four to five years. These variations in annual growth are interpreted as calving cycles. Changes in average growth rate between Wrangel Island and Chukotka specimens can be explained based on differences in ontogenetic age and a shift to an insular environment. Further analyses of tusk samples from Wrangel Island and Chukotka will allow for an increased understanding of shifts in the patterns of life histories within mammoth populations through time and will ultimately allow for greater interpretative power in deducing the cause of their extinction.